1975
DOI: 10.1007/bf00471177
|View full text |Cite
|
Sign up to set email alerts
|

Cytological differentiation of asymptomatic pancreatic islet cell tumours in autopsy material

Abstract: In eleven cases thirteen pancreatic islet cell adenomas were found in autopsy material from 1366 adult cases. Ten of the adenomas were solitary, while 3 small adenomas were observed in a single case. Another four possible solitary adenomas were observed, but their identity was uncertain owing to marked fibrosis. All the adenomas contained A-2 (A)-1 cells but no B (B)-1 cells. Nine of them also contained A-1 (D)-1 cells. The majority of cells in the adenomas were A-2 cells or cells which did not stain with any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…However, in humans, similar, clearly age-dependent changes have been observed in autopsy studies [31,32] suggesting that the Butler observations are mainly due to the age difference between the groups. The hyperplasia in the Butler study led some to think of the alpha cell hyperplasia that has been observed in mice with glucagon receptor mutations and animals treated with glucagon antagonists [33,34], based on the idea that, if GLP-1 therapies inhibit glucagon secretion, they may also cause alpha cell hyperplasia.…”
Section: Dpp-4 Dipeptidyl Peptidase-4 Glp-1 Glucagon-like Peptide-1supporting
confidence: 69%
“…However, in humans, similar, clearly age-dependent changes have been observed in autopsy studies [31,32] suggesting that the Butler observations are mainly due to the age difference between the groups. The hyperplasia in the Butler study led some to think of the alpha cell hyperplasia that has been observed in mice with glucagon receptor mutations and animals treated with glucagon antagonists [33,34], based on the idea that, if GLP-1 therapies inhibit glucagon secretion, they may also cause alpha cell hyperplasia.…”
Section: Dpp-4 Dipeptidyl Peptidase-4 Glp-1 Glucagon-like Peptide-1supporting
confidence: 69%
“…The incidence of pancreatic neuroendocrine tumours is 17% in patients with known von Hippel-Lindau disease but only 0.5%-1.5% in unselected autopsies [13]. Unlike many cases of von Hippel-Lindau disease in which the patient commonly presents with retinal angiomas and cerebellar haemangioblastomas, in the case presented here the pancreatic neuroendocrine tumour was the first and only manifestation.…”
Section: Discussionmentioning
confidence: 70%
“…The tumors show no significant gender predilection and occur at all ages, with a peak incidence between 30 and 60 years. [5][6][7] Approximately 1-2% of patients with these tumors have familial syndromes of predisposition, and the genetics of these disorders are discussed below. Figure 1 The normal endocrine pancreas.…”
Section: Epidemiologymentioning
confidence: 99%